Social Innovation and Business in Taiwan - Han, I.; Hou, Sheng-Tsung.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Based on five major research cases observed in Taiwan, this book introduces the core concept of a social innovation system to show how the common good can be established, adapted and diffused across communities, societies and national boundaries.
Keywords: Business; Ethnology -- Asia; Management; Industrial management; International business enterprises; Business ethics; Economics; Management science; International economics; Business and Management; International Business; Business Ethics; Asian Culture; International Economics; Economics, general; Innovation/Technology Management; Electronic books